Sustainable Digital Signage with Free Software: An Applied Study with Raspberry Pi in Smart Campuses - Barreto, Gabriel de Carvalho; Mignoni, Vitor Marcelo; Mazo, Pedro Vinicios; Scalco Neto, Heitor; Zanetti, Alisson Borges (Anais do Congresso Latino-Americano de Software Livre e Tecnologias Abertas (Latinoware); 2025: Anais do XXII Congresso Latino-Americano de Software Livre e Tecnologias AbertasDO - 10.5753/latinoware.2025.16544, 2025)
This paper presents Next Signage, a sustainable digital signage system designed for academic environments, utilizing open-source software, Raspberry Pi microcomputers, and repurposed hardware. The project aims to reduce electronic waste and operational costs while enhancing communication within the IFC Campus Concórdia. We adopted a Model-View-Controller (MVC) architecture to create a scalable and low-resource system. The server-side, developed in PHP, manages content playlists, while the Python-based client, running on a Raspberry Pi, handles media playback. Performance analysis of existing open-source solutions like piSignage and Chromium Kiosk revealed gaps in efficiency and user interface design, justifying the need for a custom solution. Our system demonstrates that a combination of refurbished screens and low-power computing can create an effective and environmentally responsible communication platform, contributing to the goals of a modern smart campus.